Freire's dialogicity in the light of educational and liberating internationalization (Revista Contexto & Educação, 2024)
The general objective of this study is to analyze, through the postulates of Freire's pedagogy, the principles of dialogic action as a factor of liberating resistance in the light of the internationalization with a focus on (trans)formation of human consciousness in contemporary teaching and learning spaces. Based on the assumptions of the qualitative approach, bibliographic research and review of the existing literature were chosen as a methodological procedure, taking Paulo Freire's pedagogical publications as sources, instituted between the years 1980 to 2021. The theoretical-methodological framework was anchored in Ana Freire (2021); Moacir Gadotti (2002) e Ira Shor (2021), scholars who lived with this author and brought to light the discussion and contextualization of Freire's dialogicity, paying attention to the formation, transformation and recognition of citizens as autonomous, resistant and libertarian. The results showed that 'dialogue', seen as an intrinsic condition of the human species, significantly contributes to the practice of resistance and awareness of solidarity actions with a view to experiencing fraternity, empathy and respect for others.
Keywords: Education; Freirean dialogue; Internationalization